(untitled) (Jurnal Destinasi Pariwisata, 2025)
The attraction of Melasti Beach is located in Melasti Ungasan, Ungasan, South Kuta, Bali. Every year the number of visits to this tourist attraction increases. So the aim of this research is to determine the motivation of tourists to visit the attraction of Melasti Beach. This research uses a descriptive analysis method with a qualitative approach obtained through a Likert scale. The data collection techniques used were observation, interviews, documentation and questionnaires. The data used is primary data and secondary data. The sample was determined using the Slovin formula, namely using 100 respondents. Based on research results, tourists who visit the Melasti Beach tourist attraction come from different genders, ages, occupations and origins. Tourists’ motivations for visiting the Melati Beach tourist attraction are very diverse. This is based on an analysis of 8 variables, namely, filling free time, enjoying the beauty of the beach, following trends, watching Kecak dance performances, relaxing/making the mind calm, capturing moments, due to adequate accessibility, and getting self-satisfaction. But there are several things that need to be improved, such as street lights which are quite far away. So tourists will feel comfortable and safe. There are factors that influence tourists’ motivation to visit the Melasti Beach tourist attraction, namely variations in tourist attractions, infrastructure, cleanliness and security.